2017
DOI: 10.1155/2017/7341893
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Women with Gestational Diabetes Mellitus: The LINDA-Brazil Study

Abstract: This study aimed to assess the frequency and severity of depressive symptoms and their relationship with sociodemographic characteristics in women with gestational diabetes mellitus (GDM) who participated in the LINDA-Brazil study. We conducted cross-sectional analyses of 820 women with GDM who were receiving prenatal care in the public health system. We conducted structured interviews to obtain clinical and sociodemographic information and applied the Edinburgh Postnatal Depression Scale (EPDS) to assess depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…In addition, information was obtained during the interview regarding smoking and sociodemographic characteristics. Charts were reviewed to collect data on prepregnancy weight, gestational weight, gestational age at recruitment, plasma glucose levels at diagnosis of GDM, treatment for GDM, and reproductive history …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, information was obtained during the interview regarding smoking and sociodemographic characteristics. Charts were reviewed to collect data on prepregnancy weight, gestational weight, gestational age at recruitment, plasma glucose levels at diagnosis of GDM, treatment for GDM, and reproductive history …”
Section: Methodsmentioning
confidence: 99%
“…Charts were reviewed to collect data on prepregnancy weight, gestational weight, gestational age at recruitment, plasma glucose levels at diagnosis of GDM, treatment for GDM, and reproductive history. 21,23 For descriptive analyses, age was classified into three categories (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and ≥40 years). Self-declared skin color was categorized as white, black, brown, or other, according to the Brazilian census bureau.…”
Section: Measurementsmentioning
confidence: 99%
“…It is also important to note that GDM itself is suggested to be a risk factor for peripartum depressive symptoms [ 24 , 27 , 40 42 ]. A recent systematic review of relevant epidemiological studies identified 18 studies with a sample size of 2,370,958 for review [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent comprehensive review, decreased PL levels have been suggested to be a marker for maternal obesity, while increased levels is associated with maternal diabetes [ 23 ]. In addition, several studies have also linked obesity in pregnancy and GDM to the development of peripartum depression, both antenatal and postpartum [ 24 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent comprehensive review, decreased placental lactogen levels have been suggested to be a marker for maternal obesity, while increased levels is associated with maternal diabetes [27]. In addition, several studies have also linked obesity in pregnancy and GDM to the development of peripartum depression, both antenatal and postpartum [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%